MEMBENTUK PERILAKU MODERASI BERGAMA SISWA MELALUI INTERNALISASI NILAI-NILAI ISLAM DI SMP MAMBAUS SHOLIHIN 7 BINTAN - Badrut Tamam, Mas Muhammad; Rosyad, Muh. Sabilar (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to describe the strategy of internalizing Islamic values to foster students' religious moderation attitudes at SMP Mambaus Sholihin 7 Bintan, Riau Islands. The background of this research is based on the urgency of instilling moderate religious values to counter the spread of radicalism and intolerance, which have increasingly infiltrated the educational sphere. The research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation involving teachers, students, the school principal, and the school environment. The findings indicate that the internalization of Islamic values is carried out through active learning, exemplary conduct by teachers, religious extracurricular activities, and the creation of a conducive and religious school environment. Values such as tolerance, justice, peace, and patriotism are instilled consistently through both formal and informal approaches. The challenges identified include low student awareness of the importance of moderate attitudes, limited innovation in teaching methods, and the negative influence of social media and external environments. As solutions, the school enhances teacher training, strengthens collaboration with families and the community, and utilizes media to promote moderate Islamic values. This research affirms that Islamic religious education plays a strategic role in shaping inclusive and tolerant student character. The internalization of Islamic values in schools impacts not only the cognitive domain but also the affective and psychomotor aspects of students, ultimately fostering Muslim individuals with strong character who can live harmoniously in a pluralistic society.